Implementasi Pembinaan Akhlakul Karimah Melalui Kegiatan Keagamaan di MTs Nurul Huda Mandiangin, Kabupaten Sarolangun, Provinsi Jambi - Suparno, Suparno; Fahrizal, Fahrizal (JOEAI (Journal of Education and Instruction), 2026)
This study aims to analyze the effectiveness of daily religious practices—such as congregational prayer, Quranic recitation, and dhikr—in fostering Islamic character. The research method used was descriptive qualitative with a case study approach. The results indicate that consistently implemented religious routines, supported by teacher role models and parental involvement, play a significant role in fostering religiosity, responsibility, empathy, and discipline in students. However, several obstacles remain, such as limited parental participation and varying levels of religious understanding among students. In conclusion, this study confirms that religious habituation is an effective instrument in Islamic character education, requiring synergy between the madrasah, family, and community.   Keywords: Akhlakul Karimah, Religious Habits, Teacher Role, madrasah, Islamic Character